A MYH7 variant in a five-generation-family with hypertrophic cardiomyopathy - Franke, Magda; Książczyk, Tomasz Marcin; Dux, Marta; Chmielewski, Przemysław; Truszkowska, Grażyna; Czapczak, Dorota; Pietrzak, Radosław; Bilinska, Zofia Teresa; Demkow, Urszula; Werner, Bożena (Frontiers in Genetics, 2024)
Background: Hypertrophic cardiomyopathy (HCM) is a genetic condition with a prevalence of 1:500–1:3 000. Variants in genes encoding sarcomeric proteins are mainly responsible for the disease. MYH7 gene encoding a myosin heavy chain beta, together with MYPBC3 gene are the two most commonly affected genes. The clinical presentation of this disease varies widely between individuals. This study aims to report a variant of MYH7 responsible for HCM in a five-generation family with a history of cardiac problems. Methods: The diagnosis was established according to the European Society of Cardiology HCM criteria based on two-dimensional Doppler echocardiography or cardiovascular magnetic resonance. Genetic analysis was performed using next-generation-sequencing and Sanger method. Results: The medical history of the presented family began with a prenatal diagnosis of HCM in the first child of a family with previously healthy parents. Five generations of the family had a long history of sudden cardiac death and cardiac problems. "A NM_000257.4:c.2342T>A (p.Leu781Gln) variant was detected in the MYH7 gene. It was heterozygous in the proband and in all affected individuals in a large family" The variant was present in 10 affected members of the family, and was absent in 7 members The clinical course of the disease was severe in several members of the family: three family members died of sudden cardiac death, one patient required heart transplantation, three underwent septal myectomy, and three required implantable cardioverter defibrillator (ICD) implantation. Conclusions: Herein, we report a MYH7 variant responsible for HCM. Familial HCM is inherited primarily in autosomal dominant mode, which is in accordance with our study. However, the presented family showed a broad clinical spectrum of HCM. Out of 10 family members with positive genetic testing 8 had severe presentation of the disease and 2 had a mild phenotype. This suggests that the severity of the disease may depend on other factors, most likely genetic.